أثر الانفتاح التجاري على التنمية المستدامة -دراسة حالة الاسيان 2000- 2023 - سايح ايمن; كرمادي عقبة بن نافع; كرمادي عقبة بن نافع (جامعة الوادي University of Eloued, 2025)
"تهدف هذه الدراسة إلى قياس أثر الانفتاح التجاري على التنمية المستدامة في رابطة دول جنوب شرق آسيا التي يطلق عليها اسم آسيان للفترة الممتدة من 2000 إلى 2023، حيث اعتمدت دراسة مجموعة من المؤشرات التي تربط بين الانفتاح التجاري والتنمية المستدامة، مستخدمين المنهج الوصفي التحليلي وذلك لعرض المفاهيم النظرية المتعلقة بالانفتاح التجاري وكذا التنمية المستدامة، لتخلص الدراسة في النهاية إلى مجموعة من النتائج لعل من أهمها ان الانفتاح التجاري يساعد في جذب الاستثمار الأجنبي لدول الاسيان وتشجيعه ومن خلال هذه الاستثمارات توجه الحكومات جل اهتمامها على تنمية البنى التحتية الخاصة بها كدليل على اهتمام الاسيان بالتنمية المستدامة بها. This study aims to measure the impact of trade openness on sustainable development in the Association of Southeast Asian Nations (ASEAN) for the period from 2000 to 2023. The study relied on a set of indicators linking trade openness to sustainable development, using a descriptive and analytical approach to present the theoretical concepts related to trade openness and sustainable development. The study ultimately concludes with a set of results, perhaps the most important of which is that trade openness helps attract and encourage foreign investment to ASEAN countries. Through these investments, governments focus their attention on developing their own infrastructure, as evidence of ASEAN's commitment to sustainable development.
ماستر العلوم التجارية
Keywords: الانفتاح التجاري; التنمية المستدامة; دول الآسيان; Trade openness; sustainable development; ASEAN countries.